Respuesta :
Remark
There are two ways to do this. You can graph the equations (which I have included at the end of the question using Desmos) or you can solve it algebraically which in this case is going to be slightly painful.
Algebra
Multiply the first equation by 4 and the second by 3
First Equation
4 [3x + 4y = 16]
12x + 16y = 64 (3)
Second Equation
3 [-4x - 3y = - 19]
- 12x - 9y = - 57 (4)
Add (3) and (4)
12x + 16y = 64
- 12x - 9y = -57 Add
7y = 7 Divide by 7
y = 1
Solve for x
3x + 4y = 16 Let y = 1
3x + 4(1) = 16
3x + 4 = 16 Subtract 4
3x = 12 Divide by 3
x = 12/3
x = 4
Answer
(4,1) just as the graph suggests.
![Ver imagen jcherry99](https://us-static.z-dn.net/files/dca/d2bc680461a0aa1f79e3025ebdef4867.png)
Answer:
(4,1)
Step-by-step explanation:
3x + 4y = 16
-4x - 3y = -19
4( 3x + 4y = 16)
3( -4x - 3y = -19)
Distribute
12x + 16y = 64
-12x - 9y = -57
Now subtract both equations
7y = 7
/7 on both sides
y = 1
Substitute y = 1 in one of the equations.
3x + 4y = 16
3x + 4(1) = 16
-4 on both sides
3x = 12
/3 on both sides
x = 4
Answer:
x = 4
y = 1